Localization of Neurofibrillary Tangles and Beta-Amyloid Plaques in the Brains of Living Patients With Alzheimer Disease - Shoghi-Jadid, Kooresh; Small, Gary W.; Agdeppa, Eric D.; Kepe, Vladimir; Ercoli, Linda M.; Siddarth, Prabha; Read, Stephen; Satyamurthy, Nagichettiar; Petric, Andrej; Huang, Sung-Cheng; Barrio, Jorge R. (The American journal of geriatric psychiatry, 2002)
The authors used 2-(1-{6-[(2-[18F]fluoroethyl)(methyl)amino]-2-naphthyl}ethylidene)malononitrile ([18F]FDDNP), a hydrophobic radiofluorinated derivative of 2-{1-[6-(dimethylamino)-2-naphthyl]ethylidene}malononitrile (DDNP), in conjunction with positron emission tomography to determine the localization and load of neurofibrillary tangles (NFTs) and β-amyloid senile plaques (APs) in the brains of living Alzheimer disease (AD) patients. Previous work illustrated the in vitro binding characteristics of [18F]FDDNP to synthetic β-amyloid(1–40) fibrils and to NFTs and APs in human AD brain specimens. In the present study, greater accumulation and slower clearance was observed in AP- and NFT-dense brain areas and correlated with lower memory performance scores. The relative residence time of the probe in brain regions affected by AD was significantly greater in patients with AD (n=9) than in control subjects (n=7; p=0.0007). This noninvasive technique for monitoring AP and NFT development is expected to facilitate diagnostic assessment of patients with AD and assist in response-monitoring during experimental treatments.